Untargeted metabolomics reveals the mechanism of amantadine toxicity on Laminaria japonica - Wang, Xiaohan; Lu, Yao; He, Jinxia; Li, Xiaojie; Xu, Yingjiang; Ren, Lihua; Li, Huanjun (Frontiers in Physiology, 2024)
The antiviral agent amantadine is frequently detected in seawater and marine organisms. Because of increasing concentrations, amantadine has become a contaminant of emerging concern. This compound has toxic effects on the brown algae Laminaria japonica. The effects of amantadine on the biological processes of L. japonica and the corresponding toxic mechanisms remain unclear. In this study, amantadine toxicity on L. japonica was investigated using histopathological and physiological characteristics combined with metabolomics analysis. Changes in metabolites were determined by untargeted metabolomics after exposure to 10 7 ng/L amantadine for 72 h. The catalase activity in the exposure group slightly increased, whereas the superoxide dismutase activity greatly decreased. An increase in the malondialdehyde concentration was observed after amantadine exposure, which suggested that lipid peroxidation and cell damage occurred. Metabolomics analysis showed that there were 406 differentially expressed metabolites after amantadine exposure. These were mainly phospholipids, amino acids, purines, and their derivatives. Inhibition of the glycerophospholipid metabolism affected the lipid bilayer and cell structure, which was aligned with changes in histological observation. Changes in amino acids led to perturbation of protein synthesis and induced oxidative stress through interference with glutathione metabolism and tyrosine metabolism. Amantadine also interfered with energy metabolism in L. japonica by disturbing the tricarboxylic acid cycle and purine metabolism. The results of this study provide new insights into the mechanism of amantadine toxicity on L. japonica.